Prototype Design of Bukaloka Mobile Marketplace Application Using Five Planes Method - Mahathanaya, I Gusti Ngurah Indra; Wirdiani, Ni Kadek Ayu; Rusjayanthi, Ni Kadek Dwi (Jurnal Ilmiah Merpati (Menara Penelitian Akademika Teknologi Informasi); Vol. 9, No. 2, August 2021, 2021)
Bukaloka is an application from Bali which is engaged in tourism regarding e-vouchers. The e-voucher service provided by Bukaloka allows users to easily buy and exchange e-vouchers without the need to print vouchers. The Bukaloka Marketplace application is not yet available for the mobile platform, so it does not facilitate access for mobile users. User Experience design is needed to facilitate application development, as well as user acceptance. The User Experience design method used is Five Planes so that the basic foundation that produces a prototype with a high fidelity level can be tested to resemble the final application. Testing the prototype using the User Acceptance Test Method with a Likert's Summated Rating. The result is that the Marketplace prototype gets a score of 815 which falls into the very good category range.